Anti-Bribery Disclosure Trends Among Mining Sector Stocks Listed on the Indonesia Stock Exchange - Makhdalena Makhdalena; Desi Zulvina; Yani Zulvina (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study aims to analyze the developing trend of anti-bribery disclosure among mining companies listed on the Indonesia Stock Exchange. The sample data of research is an 81 -observation firm-year period during 2017–2019. The results of the study revealed that there is increasing information about anti-bribery disclosure from year to year. The most frequently disclosed information relates to corporate whistle-blowing system policies. The results indicated that the size of the board of directors, whether the entity is a state-owned company, and the type of auditor employed by the firm are positively significant influences on a corporation’s anti-bribery disclosure. Meanwhile, profitability has a negatively significant influence on anti-bribery disclosure, and there appears to be no effect at all from either firm size or firm leverage on a company’s anti-bribery disclosure. The authors recommended that regulators consider more anti-bribery activity and require disclosure of a company’s policies as evidence of its commitment to stakeholders and to demonstrate transparency, policies, and efforts to eradicate corruption and comply with ethical standards. This proposal can be supported by governmental regulations and ISO 37001 standards to permit companies to relatively easily implement an anti-bribery management system that would be highly useful to counter the risks of corruption cases.